System for determining state of continuous welded track - Khalfin Gali-Askar; Umarov Khasan; Purtseladze Irina; Yembergenov Murat (E3S Web of Conferences, 2023)
The article considers the main disadvantages of the existing method of examining the lashes of a jointless path, in which a pedestrian bypass of the sections of the canvas and their visual control is performed. A system for monitoring the temperature stresses of jointless rail lashes laid in the path is proposed, which allows monitoring the longitudinal displacement of the track throughout the entire life cycle: from the moment the rails are welded into long-length lashes, including their laying, and throughout further operation. The system makes it possible to monitor compliance with the optimal fixing temperature of rail lashes during their laying, welding and fixing, based on data obtained with the help of sensors, to determine the actual fixing temperature in the lashes of a jointless track; to control the optimal fixing temperature of rail lashes in areas of restoration of their integrity.